Modulus-adjustable and mechanically adaptive dry microneedle electrodes for personalized electrophysiological recording - Chenzheng Zhou; Guang Yao; Xingyi Gan; Kexin Chai; Peisi Li; Jiaqi Peng; Taisong Pan; Min Gao; Zhenlong Huang; Binbin Jiang; Zongkai Yan; Kangning Zhao; et al. (npj Flexible Electronics)
Abstract Electrodes underpin electrophysiological signals recording, requiring stable skin contact and low impedance for high-quality, long-term acquisition. Dry microneedle electrodes penetrate the stratum corneum and bypass hair to ensure robust contact, but conventional rigid designs lack tissue conformity, risking discomfort and injury. This work introduces a modulus-adjustable, mechanically adaptive dry microneedle electrode (MDME) constructed from PEDOT: PSS and shape memory polymer. Submillimeter MDME penetrates skin barriers and, upon body temperature activation, softens to match tissue mechanics, minimizing invasiveness. The MDME exhibits low, stable interface impedance and enables high-quality electromyography, electrocardiography, electroencephalography, and electrocorticography recordings. After one month of usage, the electrophysiological root mean square noise increased by only 6 μV, compared to 63 μV of Ag/AgCl gel electrodes. Electroencephalogram signal-to-noise reached 8.12 dB versus 7.26 dB for the cranial screw electrodes. This work represents a notable advancement in MDME-based electrophysiological recording, expanding its potential applications in personalized healthcare and human-machine interaction.